A "blind" vascular ring in association with congenital cystic adenomatoid malformation: A case report. Issue 51 (December 2017) - Xia, Bo; Hong, Chun; Tang, Jing; Liu, Cuifen; Yu, Gang
Abstract: Rationale: The occurrence of congenital cystic adenomatoid malformation (CCAM) and vascular ring (VR) is extremely rare. Patient concerns: We present a case of left CCAM with VR consisting of a left aortic arch and right descending aorta with left tracheal compression causing atelectasis. Diagnoses: A high-risk male neonate with the diagnosis of left CCAM was diagnosed at 20 weeks gestational age by antenatal ultrasound. Chest CT revealed multiple cysts in the left inferior lung. Cardiac CT showed VR consisting of a left aortic arch and right descending aorta with left tracheal compression causing atelectasis. Interventions: left inferior lobectomy was performed. Cardiac CT showed VR consisting of a left aortic arch and right descending aorta with left tracheal compression causing atelectasis. Descending aorta transposition was performed. Outcomes: The patient recovered smoothly and remained asymptomatic during the 12-months of postoperative follow-up period. Lessons: We report this rare case of CCAM with VR consisting of left aortic arch and right descending aorta with left tracheal compression causing atelectasis. From the findings of this report, early surgical treatment is recommended. Although the prognosis after surgery remained good, second surgery can be avoided if VR was detected early.